1971
DOI: 10.1139/v71-519
|View full text |Cite
|
Sign up to set email alerts
|

Ion Pair Formation in Solutions of Alkali Halides in Dimethyl Sulfoxide: Ultrasonic Absorption Studies

Abstract: The ultrasonic absorption of dimethyl sulfoxide solutions of several alkali halides has been studied in the frequency range 1.5 to 52 MHz. An excess absorption, relaxing between 3 and 8 MHz, was observed. The relaxation was assigned to the final step in the stepwise formation of a contact ion pair, with the relaxation frequency controlled by the rate of movement of a solvent molecule rather than an ion. Data on the system water – dimethyl sulfoxide are also presented and the effect of water on the relaxation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1972
1972
1980
1980

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Dimethyl Sulfoxide. This substance has been used pure (27,66,74,122,161,193,194) and mixed with water (10,74,192) and alcohols (10) as a solvent for titration using potentiometric (27,66,161,193,194), indicator (10,193,194), and conductometric (122,192) methods. A potentiometric method for detecting thio and sulfide impurities in DMSO has been developed (144).…”
Section: Sulfatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimethyl Sulfoxide. This substance has been used pure (27,66,74,122,161,193,194) and mixed with water (10,74,192) and alcohols (10) as a solvent for titration using potentiometric (27,66,161,193,194), indicator (10,193,194), and conductometric (122,192) methods. A potentiometric method for detecting thio and sulfide impurities in DMSO has been developed (144).…”
Section: Sulfatesmentioning
confidence: 99%
“…Spectroscopic studies on solvent-solute interactions for halide ions (285,286) indicate that the preferential solvation did not occur in DMS0-H20 mixtures. Contact ion pairs were detected for solutions of alkali halides in DMSO from ultrasonic absorption studies (74). Cryoscop-ic measurements indicated that H2C2O4, CI3CCO2H, and picric acid were 100% ionized; CI2CHCO2H, 50% ionized; and C6H5CO2H, CICH2CO2H, salicyclic, tartaric, succinic, maleic, fumeric, and phthalic acids were less than 10% ionized in DMSO (3).…”
Section: Sulfatesmentioning
confidence: 99%